Convolutional neural networks for cell detection and counting : a case study of human cell quantification in zebrafish xenografts using deep learning object detection techniques - Albuquerque, Carina Isabel Andrade (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics